Microphysical Parameterization of Arctic Diamond Dust, Ice Fog, and Thin Stratus for Climate Models - Girard, Eric; Blanchet, Jean-Pierre (2001)
A parameterization is described for low-level clouds that are characteristic of the Arctic during winter. This parameterization simulates the activation of aerosols, the aggregation/coalescence, and the gravitational deposition of ice crystals/water droplets and the deposition/condensation of water vapor onto ice crystals/water droplets. The microphysics scheme uses four prognostic variables to characterize clouds: ice water content, liquid water content, and the mean diameter for ice crystals and for water droplets, and includes prognostic supersaturation. The parameterization simulates stable clouds where turbulence and entrainment are weak, like ice fogs, thin stratus, and diamond dust. The parameterization is tested into the Local Climate Model (LCM), which is the single column version of the Northern Aerosol Regional Climate Model (NARCM). NARCM is a regional model with an explicit representation of the aerosol physics and with the physics package of the Canadian Climate Center General Circulation Model version two. Since most climate models do not have prognostic size-segregated aerosol representation, an alternate method is proposed to implement the microphysical parameterization into these models. The model results are compared to observations of diamond dust and ice fog at Alert (Canada) for the period 1991–94. Two aerosol scenarios are compared in the simulation: a natural background aerosol scenario and an acidic aerosol scenario. Results show that the LCM reproduces approximately the time variation of the observed weekly frequency of the total ice crystal precipitation with a correlation coefficient of 0.4. Although it overestimates diamond dust frequency and underestimates ice fog frequency, the LCM predicts quite well the total precipitation frequency (ice fog and diamond dust added). The acidic aerosol scenario is in good agreement with the observations, showing a mean frequency of total precipitation over the 4 yr of 39% compared to the observed value of 37%. The natural aerosol scenario ...